Numerical Optimization of the Location of F1 CDG Wings - Barata, Jorge M M (2008)
In October 2005, FIA (International Automobile Federation) proposed a set of rules, for the 2008/9 Formula 1 Championship, with the objective of decreasing the difficulties for overtaking due to the wake generated by the leading car. The proposal is based on the utilization of a new concept of a double rear wing "CDG-wing" (Central Downwash Generating Wing). The objectives of this work is to analyze the aerodynamic characteristics of the CDG wing proposed by FIA, and to investigate its better positioning relative to the rear wheel. The study was performed using three different geometries of the wing, and three different speeds, to reproduce three different curves of some race tracks used in Formula 1. The computational tests have shown that the location of the wings behind the rear tire increases the downforce.